2021
DOI: 10.1007/s10578-020-01105-2
|View full text |Cite
|
Sign up to set email alerts
|

An Eye-Tracking Study of Attention Biases in Children at High Familial Risk for Depression and Their Parents with Depression

Abstract: Attention biases (AB) are a core component of cognitive models of depression yet it is unclear what role they play in the transgenerational transmission of depression. 44 children (9–14 years) with a high familial risk of depression (HR) were compared on multiple measures of AB with 36 children with a low familial risk of depression (LR). Their parents: 44 adults with a history of depression (HD) and 36 adults with no history of psychiatric disorder (ND) were also compared. There was no evidence of group diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 105 publications
(249 reference statements)
2
15
0
Order By: Relevance
“…Data were collected within a broader project on cognitive biases in youth depression (Platt, 2017). Data from the same project are reported elsewhere in relation to attention (Platt et al, 2021) and interpretation (Sfärlea et al, 2019b) biases in at-risk youth, as well as interpretation biases in clinicallydepressed youth (Sfärlea et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were collected within a broader project on cognitive biases in youth depression (Platt, 2017). Data from the same project are reported elsewhere in relation to attention (Platt et al, 2021) and interpretation (Sfärlea et al, 2019b) biases in at-risk youth, as well as interpretation biases in clinicallydepressed youth (Sfärlea et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Clinically-depressed youth, youth with an elevated familial risk of depression and youth with a low familial risk of depression were included in order to maximise variation (recommended by Everaert et al, 2017a). Since the psychometric properties of behavioural measures of cognitive biases are generally poor (Gibb et al, 2016;LeMoult & Gotlib, 2019), measures which had previously shown good reliability were selected (Platt et al, 2021;Sfärlea et al, 2019b). A measure of ER which included sub-scales for adaptive and maladaptive ER was chosen, since it is unclear whether mediating effects are specific to rumination (Everaert et al, 2017a) or also apply to adaptive ER strategies (Sanchez et al, 2016).…”
Section: The Current Studymentioning
confidence: 99%
“…Data from tasks comparing AB in MD, HR and LR youth are presented here. Data from interpretation bias tasks [38,44] and tasks comparing AB in children and parents of HR and LR groups [36] are presented elsewhere. To ensure quality of our tasks and results, we determined psychometric properties of each task and parameter and only report those with acceptable reliabilities (PVT, VST).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, psychometric properties of the PVT have been found acceptable in adults [27,35] and in youth [36]. To our knowledge, only two studies have employed this paradigm to investigate bias in sustained attention in youth depression: one found AB away from sad faces in youth with MD [21], the other found AB towards sad faces in youth at risk for MD, moderated by genetical differences in HPA-axis reactivity [24].…”
Section: Measuring Abmentioning
confidence: 99%
See 1 more Smart Citation